Sistem Pemantauan Kadar pH, Suhu dan Warna pada Air Sungai Melalui Web Berbasis Wireless Sensor Network - Ahmad Sabiq; Prabowo Nugroho Budisejati (Jurnal Teknologi dan Sistem Komputer, 2017)
Water is a very important natural resource for human life and other living things. Water pollution, especially in river water, should be controlled because of the rapid development. One technology to monitor multiple physical quantities scattered in a region is the Wireless Sensor Network (WSN). WSN technology has the ability to transmit data from sensor readings and forward data received from other nodes. In this study, a prototype was developed to monitor pH level, temperature, and color of river water based on WSN that can be monitored through the web. The sensors at each node are connected to Arduino Uno as a processing unit. Data read from the sensor is sent to the sync node via XBee wireless device. In the sink, the PC also serves as a database server and a web server is used. Test results with two different dispersion indicate that sensor readings can be read by all nodes and received by the sync node and can be displayed on web pages that have been built.